A PROSPECTIVE RANDOMIZED CONTROL STUDY COMPARING POST-OPERATIVE ANALGESIA AFTER WOUND INFILTRATION WITH ROPIVACAINE ALONE AND ROPIVACAINE WITH DEXMEDETOMIDINE IN SPINE FIXATION SURGERIES WITH PROSTHESIS - KONNUR, SHASHI RAVI; LAMBA, P. S.; SHIVI (International Journal of Current Pharmaceutical Research, 2023)
Objective: To compare postoperative analgesia after wound infiltration with ropivacaine alone and ropivacaine with dexmedetomidine in spine fixation surgeries with prosthesis. This is aprospective randomized double-blind clinical trial. Methods: A total of 60 patients were recruited in this study based on inclusion and exclusion criteria. Written informed consent was obtained from every patient. Patients were randomized by computer-generated randomization into two groups. Group R received an injection ropivacaine 0.5% in a dose of 2 mg/kg for wound infiltration, while those in group RD received an injection dexmedetomidine 0.5mcg/Kg along with ropivacaine 0.5% 2 mg/kg for wound infiltration at the end of surgery. Patients were observed till 24 h postoperatively. VAS score, duration of analgesia, total rescue analgesic consumption, any side effects were observed and noted at specified time intervals. Results: VAS score was found to be lower in group RD at any time interval till 24 h postoperatively, with a p value = 0.004. Time to first rescue analgesic demand was 281.43±11.1 min in group R while it was 912.57±52.61 min in group RD. This difference was found to be statistically significant (p value = 0.01). In group R, 200±39.39 mg of tramadol was consumed as rescue analgesic, while in group RD 136.67±28.42 mg of tramadol was consumed till 24 h post-operatively. Tramadol consumption was found to be significantly low in group RD (p =0.007). No significant side effect was observed in either of the groups. Conclusion: Based on our study, we conclude that dexmedetomidine as an adjuvant to ropivacaine for local wound infiltration improves analgesic profile, increase analgesia duration and reduces opioid requirement in patients undergoing spine surgeries with prosthesis.